ANALISIS PENGELOLAAN DANA DESA DALAM PEMBERDAYAAN MASYARAKAT PERSPEKTIF EKONOMI ISLAM (STUDI DESA RAMBAHAN, BATANGHARI, JAMBI) - Saifullah (Journal of Management and Social Sciences, 2023)
This study aims to determine whether the village government of Rambahan is economical, and to build infrastructure for community economic empowerment. This research method uses a qualitative method which is sourced from the village office of the Rambahan village government, Muara Bulian District, Batanghari Regency, Jambi. The results of the research carried out concluded that (1) The planning stage of the Village Fund Allocation in the village of Rambahan was in accordance with what was planned by the village government and in accordance with the needs of the community to improve the standard of living of the community. However, the lack of participation of the Rambahan village community in the deliberations on the Determination of the Use of the Village Fund Budget so that there are some parties who have different opinions. (2) The application of the Village Fund Allocation (ADD) for the empowerment of rural communities is appropriate in the view of Islamic economics, because it has implemented quite well the principles of ta'awun and the principle of shura according to the principles of an Islamic perspective. (3) The use of the village fund budget in Rambahan Village, Muara Bulian District can be seen from the success of the financial performance of the village fund budget in Rambahan Village in 2019-2021 in the category like this based on the category and percentage of each statement on average being in the good category andpercentage above 60% until it reaches below 80% success.